ROLE OF ANTIOXIDANT IN RECURRENT PREGNANCY LOSSES: Antioxidant in Recurrent Pregnancy Losses - Bhatti, Tufail Ahmed; Thaver, Inayat H. (Pakistan Armed Forces Medical Journal, 2017)
Objective: To compare the rate of recurrent abortion in antioxidants supplemented and non-supplemented mothers.Study Design: Randomized control trail, double blind study.Place and Duration of Study: Liaquat University Medical and Health Sciences-Jamshoro (LUMHS), Shaheed Mohtarma Benazir Bhutto Medical University Larkana (SBBMU) hospital and PMC hospital Nawabsha (2012-2014).Material and Methods: The patients were the mothers who had aborted three consecutive losses continuously. It was multicentre hospitals based study, where cases of recurrent abortion mothers frequently reported and were available. Two techniques were used convenient and snowball to select the patients.Results: A total of 123 cases of recurrent abortion (RA) were recruited and identified for registration (Point Estimate of Incidence) among them n=67 mothers in the active arm and n=56 in placebo arm. The R.A incidence rate was 89 per 1000 mothers at risk in Placebo arm and 149 per 1000 mothers at risk in Active arm. In case of RA the mean age was 30 years in both the arms. Mothers who had suffered recurrent abortion in both arms were mostly illiterate (61%). The mean duration of marriage in active arm was 16.7 years. Researcher found that most of mothers, 92 (75%) did not become pregnant after taking the prescribed supplementation.Conclusion: The use of antioxidants before conception and during pregnancy significantly improves the chances of live births and outcome in general.